2006
DOI: 10.1902/jop.2006.77.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Administration of Monosodium Olpadronate on Experimental Periodontitis in Rats

Abstract: The dose used herein was found to inhibit bone loss and to cause marked morphologic changes in osteoclasts. The drug effectively prevented bone loss caused by periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
(33 reference statements)
4
28
0
Order By: Relevance
“…### P \ 0.001 vs. experimental periodontitis model widely used to study periodontal disease is by fixing ligatures around the teeth. This animal model has characteristics for the disease process that are similar to those encountered in humans [38][39][40]. In severe degrees of periodontitis, the lesions affect the inter-radicular and inter-dental spaces with extensive alveolar bone resorption and denudations of the molar roots [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…### P \ 0.001 vs. experimental periodontitis model widely used to study periodontal disease is by fixing ligatures around the teeth. This animal model has characteristics for the disease process that are similar to those encountered in humans [38][39][40]. In severe degrees of periodontitis, the lesions affect the inter-radicular and inter-dental spaces with extensive alveolar bone resorption and denudations of the molar roots [41].…”
Section: Discussionmentioning
confidence: 99%
“…The cotton thread ligature was pushed into the gingival sulcus and was left in place for two weeks until death [32].…”
Section: Methodsmentioning
confidence: 99%
“…Each mandible was then processed for paraffin embedding, and 4-m-thick sections were obtained for each. The first section was stained with hematoxylin and eosin (H&E) for histological observations, while the next serial section was stained with tartrate-resistant acid phosphatase (TRAP) to reveal osteoclasts, which are considered to be TRAP-positive multinucleated cells (35)(36)(37). The number of osteoclasts on the interradicular septum (bone surface) (Oc.N/BS) was determined, and the osteoclast surface on the interradicular septum (bone surface) (Oc.S/BS) was evaluated, by scoring the TRAP-positive multinucleated cells attached to the bone surface as defined by Parfitt et al (38,39).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the necessity of preventing alveolar bone resorption in such patients, no practical means of inhibition is available, so experimental models of periodontitis play a pivotal role in the development of inhibitors of alveolar bone resorption in periodontitis. Several studies have reported periodontitis in experimental animals and have focused on induction of periodontitis by persistent bacterial challenge via repeated administration of bacteria, bacterial components, or bacterial products (oral gavage model) [1][2][3][4][5][6] or creation of a subgingival environment prone to food impaction by using modifying devices, such as cotton ligatures [7][8][9][10][11][12] . However, many of these experimental models have disadvantages when establishing induced periodontitis.…”
Section: Introductionmentioning
confidence: 99%